Young people's comfort receiving sexual health information via social media and other sources. (December 2014) - Lim, Megan SC; Vella, Alyce; Sacks-Davis, Rachel; Hellard, Margaret E
Social media are growing in popularity and will play a key role in future sexual health promotion initiatives. We asked 620 survey participants aged 16 to 29 years about their time spent using social media and their comfort in receiving information about sexual health via different channels. Median hours per day spent using social network sites was two; 36% spent more than 2 hours per day using social network sites. In multivariable logistic regression, being aged less than 20 years and living in a major city (compared to rural/regional Australia) were associated with use of social media more than 2 hours per day. Most participants reported being comfortable or very comfortable accessing sexual health information from websites (85%), followed by a doctor (81%), school (73%), and the mainstream media (67%). Fewer reported being comfortable getting information from social media; Facebook (52%), apps (51%), SMS (44%), and Twitter (36%). Several health promotion programmes via social media have demonstrated efficacy; however, we have shown that many young people are not comfortable with accessing sexual health information through these channels. Further research is needed to determine how to best take advantage of these novel opportunities for health promotion.